Optimization of square shape portable vacuum clamping (Square) based on machining parameter - Ab Wahab, Norfariza; Basharudin, Shiradzi; Md Nasir, Nur Syuhada; Ruslan, Eliyana; Abdul Hadi, Dayanasari; Boejang, Hambali (Asian Research Publishing Network (ARPN), 2019)
Clamping is a fastening device function to hold or secure the object to prevent movement during process or when applied pressure. There are many types of clamping device available for many purposes. This project purpose is to optimize the vacuum clamping based on the machining parameter. From the previous research that develop the vacuum clamping, the product is continue to use to determine the machining performance of vacuum clamping. However, at that time the target was only to develop a functional prototype and only some testing were done. Therefore, in order to optimize the vacuum clamping surface roughness testing was done using this new clamping device to compare with existing clamping device. The expected result show that vacuum clamping is better. As a conclusion, vacuum clamping can be improved for better use in the future and apply to the manufacturing field.